A Comparative Study between Chang’an School of Flower-and-Bird Paintings and Western Still Life Paintings - Xue, Gao; Misdih, Musnin Bin (Journal of Ecohumanism, 2024)
This comparative study examines the stylistic, thematic, and cultural differences between the Chinese Chang’an School of Flower-and-Bird Paintings and Western Still Life Paintings. The analysis of differences in the visual approaches, philosophical underpinnings, and symbolic elements innate in each of the traditions elaborates how these two art forms reflect their cultural contexts. The Chang’an School, strongly attached to Confucian and Taoist thoughts, draws more attention in its balanced, harmonious relation with nature, while Western still life mainly focuses on realism, materiality, and transience in most works of the Renaissance and Baroque. This analysis follows theoretical frameworks such as the Iconology of Panofsky, the Cultural Ecology of Steward, and the Aesthetics of Ye Lang for insight into the cultural and historical philosophical influences on such artistic practices to explore how visual symbolism has communicated cultural values in both traditions through case studies of representative works by Shi Lu, Jiang Wenzhan, Claude Monet, and Henri Fantin-Latour.